2008
DOI: 10.1007/s10620-008-0622-2
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Obestatin Levels in Type 2 Diabetic Patients With and Without Delayed Gastric Emptying

Abstract: Alterations in the neurohumoral regulation of the upper intestine may change rhythmicity and pattern of ghrelin and obestatin, the latter presumably antagonizing ghrelin effects. Five nongastroparetic diabetic patients and five with gastroparesis were investigated. Over 390 min including breakfast and lunch, ghrelin was significantly lower in patients with gastroparesis compared with in those without (P = 0.015). Ghrelin subsequent to lunch decreased significantly (P = 0.011) in patients without gastroparesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…With peripheral and central administration, obestatin was found to antagonize ghrelin's effects on food intake, body weight, and gastric emptying, but not on GH levels 28. Studies on obestatin/ghrelin ratio in the GI tract and plasma have been reported to be associated with some disease such as irritable bowel syndrome (IBS), obesity, and type II diabetes mellitus 29-31…”
Section: Ghrelin-family Peptides and Receptorsmentioning
confidence: 99%
“…With peripheral and central administration, obestatin was found to antagonize ghrelin's effects on food intake, body weight, and gastric emptying, but not on GH levels 28. Studies on obestatin/ghrelin ratio in the GI tract and plasma have been reported to be associated with some disease such as irritable bowel syndrome (IBS), obesity, and type II diabetes mellitus 29-31…”
Section: Ghrelin-family Peptides and Receptorsmentioning
confidence: 99%
“…Studies in humans did not show differences in the microscopic appearance of the subdiaphragmatic vagus in diabetic patients [94]. However, the postprandial increase in PPY and ghrelin is blunted or absent in patients with diabetic or postsurgical gastroparesis, but not idiopathic gastroparesis, suggesting that the function rather than the light-microscopic structure of vagal pathways is abnormal in this subset of patients [95, 96]. Looking beyond just vagal pathways, several investigators described changes in nerve fiber density within the stomach or ultrastructural changes in nerve fibers of patients with gastroparesis [97100].…”
Section: Disease Mechanismsmentioning
confidence: 99%
“…Contrary to the mentioned findings, a recent study showed that long-term increase in blood glucose or hyperglycemia reduces ghrelin secretion (9). In another study, too, no interaction was observed between ghrelin and food intake and energy regulation, at least in diabetic patients (10). The findings of another study indicate that a low-dose i.v.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, imbalance in secretion of certain peptide hormones, by adipose tissue such as cytokines or ghrelin and obestatin level can not be ignored in increasing blood glucose in diabetic patients (8,9). At the same time, ghrelin is a hormone implicated in hunger and long-term regulation of body weight (10). The plasma levels of this 28amino-acid peptide hormone increases shortly before meals and reduces shortly after meals (11).…”
Section: Introductionmentioning
confidence: 99%